Structural features of α-synuclein amyloid fibrils revealed by Raman spectroscopy - Flynn, Jessica D.; McGlinchey, Ryan P.; Walker, Robert L.; Lee, Jennifer C. (The Journal of biological chemistry, 2018)
Parkinson’s disease (PD) is associated with the formation of α-synuclein amyloid fibrils. Elucidating the role of these β-sheet-rich fibrils in disease progression is crucial; however, collecting detailed structural information on amyloids is inherently difficult because of their insoluble, non-crystalline, and polymorphic nature. Here, we show that Raman spectroscopy is a facile technique for characterizing structural features of α-synuclein fibrils. Combining Raman spectroscopy with aggregation kinetics and transmission electron microscopy, we examined the effects of pH and ionic strength as well as four PD–related mutations (A30P, E46K, G51D, and A53T) on α-synuclein fibrils. Raman spectral differences were observed in the amide-I, amide-III, and fingerprint regions, indicating that secondary structure and tertiary contacts are influenced by pH and to a lesser extent by NaCl. Faster aggregation times appear to facilitate unique fibril structure as determined by the highly reproducible amide-I band widths, linking aggregation propensity and fibril polymorphism. Importantly, Raman spectroscopy revealed molecular-level perturbations of fibril conformation by the PD–related mutations that are not apparent through transmission electron microscopy or limited proteolysis. The amide-III band was found to be particularly sensitive, with G51D exhibiting the most distinctive features, followed by A53T and E46K. Relating to a cellular environment, our data would suggest that fibril polymorphs can be formed in different cellular compartments and potentially result in distinct phenotypes. Our work sets a foundation toward future cellular Raman studies of amyloids.